2015
DOI: 10.1021/acs.jafc.5b01441
|View full text |Cite
|
Sign up to set email alerts
|

Sesamol Enhances Cell Growth and the Biosynthesis and Accumulation of Docosahexaenoic Acid in the Microalga Crypthecodinium cohnii

Abstract: Sesamol is a strong antioxidant phenolic compound found in sesame seed. It possesses the ability to scavenge intracellular reactive oxygen species (ROS) and to inhibit malic enzyme activity and NADPH supply, resulting possibly in cell proliferation and alteration in the fatty acid composition. In the present study, the effect of sesamol on the growth and accumulation of docosahexaenoic acid (DHA) was investigated in the marine microalga Crypthecodinium cohnii, a prolific producer of DHA. C. cohnii showed a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 36 publications
8
37
0
Order By: Relevance
“…These results indicated that more of the malate could enter the TCA cylce to produce the acetyl-CoA precursor citrate ( Figure 5). Although downregulated malic enzyme reduces the production of NADPH, recent studies have shown that the NADPH produced by malic enzyme enters exclusively into the FAS pathway for SFA biosynthesis and is not involved in the PKS pathway for PUFA biosynthesis [35,36]. Downregulated ME coupled with decreased SFA content was also observed in this study.…”
Section: Transcriptomic Profiling Under Cold Temperaturessupporting
confidence: 72%
“…These results indicated that more of the malate could enter the TCA cylce to produce the acetyl-CoA precursor citrate ( Figure 5). Although downregulated malic enzyme reduces the production of NADPH, recent studies have shown that the NADPH produced by malic enzyme enters exclusively into the FAS pathway for SFA biosynthesis and is not involved in the PKS pathway for PUFA biosynthesis [35,36]. Downregulated ME coupled with decreased SFA content was also observed in this study.…”
Section: Transcriptomic Profiling Under Cold Temperaturessupporting
confidence: 72%
“…d (p < 0.05 or 0.01), and the highest enduracidin production was achieved by Vc with the addition time at 4 d. However, addition of 130 mM Vc had a negative effect on enduracidin production at four different phases, indicating that high Vc concentration inhibited enduracidin accumulation in S. fungicidicus M30. Similar results have also been reported in previous studies[19,20]. The result indicates that the addition of 90 mM Vc can promote enduracidin accumulation in S. fungicidicus M30.…”
supporting
confidence: 91%
“…SUN were achieved at 96 h of cultivation under light conditions (Sun et al 2017). Under sesamol supplementation, highest biomass (3.9 g/L), TFA (21% DCW), DHA (41.3% TFA) and DHA productivity (58 mg/L day) was attained in C. cohnii ATCC 30556 (Liu et al 2015). Pleissner and Eriksen (2012) reported highest biomass (2.1 g/L), TFA (111 mg/g) and DHA contents (36.2% TFA) in C. cohnii CCMP 316 when cultured on acetic acid as major carbon source.…”
Section: Discussionmentioning
confidence: 99%
“…Many of studies were reported evaluating the effect of nutrients and factors such as glucose, carbon, culture temperature, salinity and light etc. for lipid production in C. cohnii (DeSwaaf et al 2003; Gong et al 2015; Liu et al 2015; Liu et al 2016a, b; Pleissner and Eriksen 2012; Ratledge et al 2001; Silva et al 2016; Sun et al 2017). In resent researches, the effect of N has been positively exploited in Monoraphidium sp.…”
Section: Introductionmentioning
confidence: 99%